Selection of rhizobium strains, inoculated in corn (Zea mays, L.), in field conditions in cattle ecosystems of Sancti Spiritus, Cuba - B?cquer, C. J.; Salas, Beatr?z; ?vila, U.; Palmero, L.; N?poles, J. A.; Ulloa, Lisbet; Su?rez, Yanet; Colina, Olga L. (Cuban Journal of Agricultural Science, 2011)
In order to select rhizobia inoculated in corn, a field trial was performed in the environmental conditions of Sancti Spiritus, Cuba. Ten native strains belonging to Bradyrhizobium sp. were applied, as well as three commercial ones of Sinorhizobium fredii, B. lupini, and Bradyrhizobium sp. The T-66 corn hybrid variety (Zea mays, L) was evaluated. A complete random block design was used, with 15 treatments and four replicates. The analysis of variance and the differences between means were applied, according to LSD of Fisher (P < 0.05). In aerial dried weight, all the inoculated treatments had values statistically higher than the non-inoculated control. The treatments inoculated with the JJ4, JJ2, SP6, HA1, HG2, SP20, and TE4 native strains, as well as the inoculated, with the 25B6 and ATCC 10317 commercial strains, showed similar superscripts in respect to the fertilized control as to the aerial dried weight. For the stalk length, the 10 inoculated treatments were statistically superior to the absolute control. Except the treatments inoculated with the SP21 native strain and the 61B7commercial strain, the other inoculated treatments were statistically superior to the absolute control as to the corncob weight. It was concluded that the inoculation with rhizobia equaled the effects of the chemical fertilization, although the result was not the same for all the variables and for the two genera of rhizobia applied either. It was proved that the inoculation favored the production of seeds in respect to other agro-productive variables of the plant. The JJ4, JJ2, SP6, HA1, and SP20 strains are recommended, as well as the 25B6 commercial strains for corn crops, in edaphic and climatic conditions similar to those of this trial, with chemical fertilization of 80 kgN/ha. Key words: Bradyrhizobium, Sinorhizobium, corn, inoculation, seeds.